تحديد المستوى البدني من خلال بطارية اختبارات للاعبي كرة اليد بأعمار "17-19" سنة في الجزائر - شهاب, بشار غالب; خالد, بعوش (Sulaimani Journal for Humanities, 2018)
The study aimed to determine the physical level of the handball players category of 17-19years through battery tests, because reaching the upper levels does not come by chance or random ways but comes scientific foundations The use of battery tests periodically in modules ensures the success of the latter and thus fly performance physical players, and I have this study was conducted in three (03) teams from the state of Bouira handball were chosen in a "deliberate", using descriptive and analytical approach through the application of physical tests on the players, and was relying on spss program in the analysis of the search results In the latter resulted in the results of the study about the health of the proposed hypotheses and revealed the fact that the contribution of the use of battery tests to determine the physical level of the players, but the results showed that the overall physical level of the teams under consideration is characterized by a weak level, and the researcher recommended that the obligation to apply battery tests to identify and measure the physical level of football players hand, air battery standardized tests by the players capabilities, reliable trainers to know the level of handball players as all categories, as well as to develop a unified standard levels for handball players in order to be a reference for field work.